Ruptured Ovarian Ectopic Pregnancy in a Patient with Recurrent Early Pregnancy Loss: A Rare Clinical Encounter - Fitra R., Muhammad; Putra, Dhifa D.; Rahmi, Trisha A.; Poempida, Fayka (JurnalMU: Jurnal Medis Umum, 2025)
Introduction: Ovarian pregnancy is a rare but serious condition, accounting for 0.5% to 1% of ectopic pregnancies. Patients presents with abdominal pain and may lack vaginal bleeding, making diagnosis difficult. Ultrasound detection is low, and surgical management is frequently required due to complications like severe bleeding. This case report aims to highlight the clinical features of ovarian pregnancy and support effective management of similar cases. Case presentation: A 37-year-old woman on her fourth pregnancy at 5 weeks of gestation presented with six days of intermittent vaginal bleeding and mild abdominal cramps. She had no prior pregnancy testing or contraceptive use. Her obstetric history included three early miscarriages, two following IVF. Examination showed elevated blood pressure but no abdominal tenderness. Transvaginal ultrasound revealed a gestational sac-like structure in the left ovary with a positive ring of fire sign, and β-hCG was 505 mIU/mL. She was diagnosed with a ruptured left ovarian ectopic pregnancy and underwent emergency laparoscopy, confirming hemoperitoneum, left ovarian ectopic mass, and mild endometriosis. Conclusion: A ruptured ovarian pregnancy can cause life-threatening hemorrhage, necessitating prompt diagnosis and intervention. Increased reporting of confirmed cases is essential to improve understanding, diagnostic accuracy, and establish effective preoperative evaluation and management strategies. Keywords: Ovarian Pregnancy, Ruptured Ectopic Pregnancy, Recurrent Early Pregnancy Loss, Habitual Abortion